Treatment Failure After Image-Guided Percutaneous Radiofrequency Ablation (RFA) of Renal Tumors – A Systematic Review with Description of Type, Frequency, Risk Factors and Management - Vollherbst, Dominik; Bertheau, Robert; Kauczor, Hans-Ulrich; Radeleff, Boris Alexis; Pereira, Philippe L.; Sommer, Christof-Matthias (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Background Radiofrequency ablation (RFA) is an established treatment for small renal tumors. The objective of this review is to systematically assess the type, frequency, risk factors and management of treatment failure after image-guided percutaneous RFA of renal tumors.Method 10 studies (967 patients, 1033 tumors) with a mean/median follow-up of ≥ 30 months were systematically identified and analyzed.Results and Conclusion Image-guided percutaneous RFA of localized renal tumors is very effective. The most common type of treatment failure is residual unablated tumor (5.9 %), followed by local tumor progression (4.7 %). De novo tumors in the kidneys occur in 1.3 % of cases and extra-renal metastases in 2.0 %. Local tumor progression, de novo tumors in the kidneys and extra-renal metastases occur predominantly later than 12 months after initial RFA. Tumor size > 3 cm and central tumor location are the major risk factors for treatment failure. In the case of treatment failure, repeated RFA shows high success rates (86.3 % for residual unablated tumors and 87.5 % for local tumor progression).Key Points:Citation Format
Keywords: radiofrequency ablation (RFA, RF ablation); tumor ablation (TA); image-guided; renal tumor; kidney